The influence of convenience, perceived ease of use, perceived risk, and security on trust with financial well-being as mediation for OVO digital payment users - Gian Mulkiansyah; Rahmiati, Rahmiati; Fasyni, Awisal (Marketing Management Studies, 2024)
This study aims to examine how convenience, perceived usability, perceived risk, and perceived security affect trust with financial wellbeing in OVO digital payment consumers. A total of 200 respondents took part in the study, and SmartPLS conducted the data analysis. The following details were included in the study's conclusions. (1) Convenience has a strong favorable impact on financial well-being. (2) There is a considerable beneficial relationship of perceived ease of use on financial well-being. (3) There is a considerable positive influence of perceived risk on financial well-being. (4) Financial well-being is positively impacted by security. (5) There is a considerable favorable influence of financial well-being on trust.